2015
DOI: 10.1371/journal.pone.0134518
|View full text |Cite
|
Sign up to set email alerts
|

Modulation and Apoptosis of Neutrophil Granulocytes by Extracorporeal Photopheresis in the Treatment of Chronic Graft-Versus-Host Disease

Abstract: Chronic graft-versus-host disease (cGVHD) is a common side effect of allogeneic stem cell transplantation and a major cause of morbidity and mortality in affected patients. Especially skin, eyes and oral mucosa are affected. This can lead to pain and functional impairment. Extracorporeal photopheresis (ECP) is an effective immunomodulatory therapy with minimal side effects but its mode of action is still largely unknown. The objective of the present study was to examine the effects of ECP on neutrophil granulo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
38
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(43 citation statements)
references
References 50 publications
4
38
1
Order By: Relevance
“…While it is known, that ECP shows clinical effectiveness in these diseases, not much is known about the effects of ECP on neutrophils, which account for the majority of treated cells during ECP. In a previous study, we showed that the majority of neutrophils treated by ECP undergo apoptosis and release arginase‐1 . In the present study, we could show that ECP‐treated neutrophils do not contribute to T cell activation and that activation of T lymphocytes by other stimuli can be suppressed by ECP‐treated neutrophils, showing a potential mechanism of how they can further contribute to ECP's clinical efficacy.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…While it is known, that ECP shows clinical effectiveness in these diseases, not much is known about the effects of ECP on neutrophils, which account for the majority of treated cells during ECP. In a previous study, we showed that the majority of neutrophils treated by ECP undergo apoptosis and release arginase‐1 . In the present study, we could show that ECP‐treated neutrophils do not contribute to T cell activation and that activation of T lymphocytes by other stimuli can be suppressed by ECP‐treated neutrophils, showing a potential mechanism of how they can further contribute to ECP's clinical efficacy.…”
Section: Discussionsupporting
confidence: 56%
“…Besides apoptosis of alloreactive cells, induction of regulatory T cells, and shift from pro‐ to anti‐inflammatory cytokines, the proposed underlying mechanisms also include the induction of dendritic cells (DC) from monocytes through interaction with the plastic chamber . In a recent study, we could show that neutrophil granulocytes account for the majority of cells treated during ECP, lose their inflammatory properties upon chemoirradiation, and partially undergo apoptosis after ECP . In the present study, we systematically analyzed the interaction of ECP‐treated neutrophils and CD3+ lymphocytes with APC.…”
Section: Introductionmentioning
confidence: 97%
“…The impact of the granulocytes in the product is also not known. Recently, Franklin et al showed that granulocytes may significantly contribute to the overall immunomodulatory effects attributed to the ECP treatment …”
Section: Discussionmentioning
confidence: 99%
“…Although poorly understood and multifactorial, its mechanism of action results from methoxypsoralen binding to leucocyte DNA leading to cell cycle arrest and apoptosis. Low numbers of apoptotic cells reintroduced into the circulation are phagocytosed by antigen‐presenting cells and may induce tolerance …”
Section: Introductionmentioning
confidence: 99%
“…Low numbers of apoptotic cells reintroduced into the circulation are phagocytosed by antigen-presenting cells and may induce tolerance. 8 Although conventional intensified immunosuppressive therapy for refractory GVHD increases mortality and relapse after allogeneic hematopoietic stem cell transplantation, ECP represents a potentially well-tolerated therapeutic approach for multiple organs as chronic GVHD involves skin, mouth, eye, and liver, with less frequent involvement of lung, gastrointestinal tract, joint/fascia, and genital tract. 9 Although ECP is available in 200 medical centers, there is still no consensus on its advantages over other treatments, optimal timing, schedule, and patient populations.…”
Section: Introductionmentioning
confidence: 99%